A case of bilateral empyema with pericardial effusion caused by streptococcus intermedius in an immunocompetent patient (Indian Journal of Case Reports, 2019)
Streptococcus intermedius, a member of the Streptococcus anginosus group and a part of the human oropharyngeal microbiome, is a recognised pathogen, mostly in immunocompromised patients or post gastrointestinal surgery, known to cause suppurative metastatic abscesses. We present an unusual case of bilateral empyema with pericardial effusion caused by Streptococcus intermedius in a healthy 30-year-old adult male patient with no known predisposing factors.This case report illustrates the ability of S. intermedius to produce life-threatening empyema in a healthy adult without any predisposing factors.